A different strategy for coupling of finite and boundary element methods - Guzelbey, Ibrahim H.; Kanber, Bahattin (Computer Assisted Methods in Engineering and Science, 2004)
In this study, a different coupling strategy is used for the coupling of finite element (FE) and boundary element (BE) methods. In the literature, the coupling is done by transforming nodal forces into nodal tractions using distribution matrix at the interface line. In this study, however, the stress-traction equilibrium is used at the interface line for coupling of both methods. A finite and boundary element program is written using FORTRAN 95 and ordinary and developed coupling methods are adapted to this program. The results of both methods are compared with each other, ANSYS, FE, BE and analytical solution whenever possible. It has been seen that the developed method supply more efficient results against the ordinary method.